Improving the student learning experience through dialogic feed-forward assessment. Issue 1 (2nd January 2020) - Hill, Jennifer; West, Harry
Abstract: Assessment feedback from teachers gains consistently low satisfaction scores in national surveys of student satisfaction, with concern surrounding its timeliness, quality and effectiveness. Equally, there has been heightened interest in the responsibility of learners in engaging with feedback and how student assessment literacy might be increased. We present results from a five-year longitudinal mixed methods enquiry, thematically analysing semi-structured interviews and focus groups with undergraduate students who have experienced dialogic feed-forward on a course in a British university. We use inferential statistics to compare performance pre and post-assessment intervention. The assessment consisted of submitting a draft coursework essay, which was discussed and evaluated face-to-face with the course teacher before a self-reflective piece was written about the assessment process and a final essay was submitted for summative grading. We evidence that this process asserted a positive influence on the student learning experience in a number of inter-related cognitive and affective ways, impacting positively upon learning behaviour, supporting student achievement and raising student satisfaction with feedback. We advocate a cyclic and iterative approach to dialogic feed-forward, which facilitates learners' longitudinal development. Programme teams should offer systematic opportunities across curricula for students to understand the rationale for and develop feedback literacy.